The Alternative Electron Acceptor Tetrathionate Supports B(12)-Dependent Anaerobic Growth of Salmonella enterica Serovar Typhimurium on Ethanolamine or 1,2-Propanediol - Price-Carter, Marian (American Society for Microbiology, 2001)
Synthesis of cobalamin de novo by Salmonella enterica serovar Typhimurium strain LT2 and the absence of this ability in Escherichia coli present several problems. This large synthetic pathway is shared by virtually all salmonellae and must be maintained by selection, yet no conditions are known under which growth depends on endogenous B(12). The cofactor is required for degradation of 1,2-propanediol and ethanolamine. However, cofactor synthesis occurs only anaerobically, and neither of these carbon sources supports anaerobic growth with any of the alternative electron acceptors tested thus far. This paradox is resolved by the electron acceptor tetrathionate, which allows Salmonella to grow anaerobically on ethanolamine or 1,2-propanediol by using endogenously synthesized B(12). Tetrathionate provides the only known conditions under which simple cob mutants (unable to make B(12)) show a growth defect. Genes involved in this metabolism include the ttr operon, which encodes tetrathionate reductase. This operon is globally regulated by OxrA (Fnr) and induced anaerobically by a two-component system in response to tetrathionate. Salmonella reduces tetrathionate to thiosulfate, which it can further reduce to H(2)S, by using enzymes encoded by the genes phs and asr. The genes for 1,2-propanediol degradation (pdu) and B(12) synthesis (cob), along with the genes for sulfur reduction (ttr, phs, and asr), constitute more than 1% of the Salmonella genome and are all absent from E. coli. In diverging from E. coli, Salmonella acquired some of these genes unilaterally and maintained others that are ancestral but have been lost from the E. coli lineage.